2022
DOI: 10.3390/jpm12081267
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacists’ Involvement in Pharmacogenomics Testing and Related Services in China

Abstract: Background: Pharmacogenomics (PGx) testing is increasingly used in clinical practice to optimize drug therapies. This study aims to understand the involvement of clinical pharmacists in PGx testing at tertiary hospitals in China and their self-assessed capacity to deliver such services. Methods: We developed a questionnaire exploring clinical pharmacists’ involvement and self-assessed level of capacity of performing PGx tests. A random sample was obtained from the Pharmaceutical Affairs Management Professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…The survey contains 38 questions and takes an estimated 10–15 min to complete. The questionnaire has been mentioned in our previously published study [ 21 ]. In this paper, we report findings from the first and third sections (24 questions) of the survey, focusing on the attitude and knowledge of pharmacists.…”
Section: Methodsmentioning
confidence: 99%
“…The survey contains 38 questions and takes an estimated 10–15 min to complete. The questionnaire has been mentioned in our previously published study [ 21 ]. In this paper, we report findings from the first and third sections (24 questions) of the survey, focusing on the attitude and knowledge of pharmacists.…”
Section: Methodsmentioning
confidence: 99%
“…Similar study in Kingdom of Saudi Arabia showed that only 16% of the students could identify drugs that require PGx testing, but 36% students were willing to use PGx testing before prescribing drug ( 49 ). Surprisingly, a recent survey in China showed that 99.1% of pharmacists participated in the study knew about PGx testing and 59% had been involved in PGx testing related services ( 50 ). Similarly, with increased awareness and support, it is likely that PGx will be widely adopted in clinical practice in India in the future ( 51 ).…”
Section: Educational Activities To Support Pgx Implementation In Qatarmentioning
confidence: 99%
“…Frontiers in Pharmacology frontiersin.org doctor school year (Zhang J. et al, 2021). Hu et al also reported that approximately 60% of pharmacists believed they had poor or fair capacity to offer PGx testing and related services (Hu et al, 2022). In Japan, only 12.4% of pharmacists had received specific PGx-related education (Tsuji et al, 2021).…”
Section: The Situation Of Responsible Departments Of Tdm and Pgx Testingmentioning
confidence: 99%